(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2016)
The study examined the relationship between being innovative and customer retention in upscale restaurants in the hospitality industry in Port Harcourt, Rivers State, Nigeria. The specific objectives were to determine the relationship between being innovative and low customer defection, repeat purchase and high referrals. The study adopted quasi-experimental design which employed survey approach gathered data from 144senior employees who work in 24 upscale restaurants in Port Harcourt. The research instrument containing 26 items, with 3 demographic items was used to elicit primary data from the respondents. After data editing, and reliability analysis of the instrument, inferential statistics was conducted with the help of Statistical Package For Social Sciences (SPSS). The inferential statistical analysis provided that following results: being innovative had positive and significant relationship with the three measures of customer retention (low customer defection, repeat purchase and high referrals respectively). The study concluded that innovativeness provides the platform to satisfy customers and hence achieve customer loyalty. It is therefore recommended that organizational managers in upscale restaurants should focus more on innovation in terms of new products and services in order to provide superior value to customers than competitors do.